Investigating the psychometric properties of the Iranian version of the Post- Secondary Student Stressors Index - Majid Yousefi Afrashteh; Seyedeh Mohadeseh Sadidi Shal (مطالعات روانشناسی تربیتی)
Nowadays, due to the complexity of societies, many factors cause stress. Especially when students move from school to college, they are vulnerable to stress in order to be in a new environment. Therefore, the aim of the present study was to investigate the psychometric properties of the Post- Secondary Student Stressors Index (PSSI), i.e. reliability, validity, confirmation of its factorial structure in the student population of University of Zanjan in the academic year 2020. PSSI is a 43-item self-assessment questionnaire and has five subscales: academic, learning environment, culture-university environment, interpersonal and personal. 345 students were selected by convenience sampling and according to Cochran Cochran's sample size formula and completed the student life stress scale. In order to determine the validity of the construct using the factor analysis method, Cronbach's alpha coefficients were used to determine the internal consistency. In order to analyze the data, reliability through Cronbach's alpha coefficient for five scales: education, learning environment, university environment culture, interpersonal and personal communication, respectively 0.80, 0.82, 0.80, 0.78 and 0.88. was obtained. Convergent validity was estimated through the correlation of PSSI with the score obtained from the Godzella student stress questionnaire, and the correlation between the total score of the two tests was 0.64, which is statistically significant (P<0.05). The construct validity of PSSI was also checked and modified through confirmatory factor analysis. In general, it can be concluded that the student stress scale is a valid and reliable tool for measuring student stress.